Synthetic and analytical strategies for the quantification of phenyl‐γ‐valerolactone conjugated metabolites in human urine - Brindani, Nicoletta; Mena, Pedro; Calani, Luca; Benzie, Iris; Choi, Siu‐Wai; Brighenti, Furio; Zanardi, Franca; Curti, Claudio; Del Rio, Daniele (Molecular nutrition & food research, 2017)
Scope The contribution of the gut microbiota to the metabolism of catechins and proanthocyanidins remains unclear. Phenyl‐γ‐valerolactones have been identified as the most representative metabolites of these dietary flavan‐3‐ols, but their accurate quantification has posed problems because of a lack of appropriate bioanalytical standards. This work aimed at synthesizing a novel set of sulphate‐ and glucuronide‐conjugated phenyl‐γ‐valerolactones and at developing an analytical platform using UHPLC‐ESI‐MS/MS for their quantification in urine. Methods and results Eight glucuronide and sulphate conjugates of hydroxyphenyl‐γ‐valerolactones were synthesized and used as analytical standards, together with five phenyl‐γ‐valerolactone aglycones, for the development of a high‐throughput, validated analytical method. Chromatographic and MS conditions were optimized. The method validation showed acceptable linearity, intra‐day and inter‐day repeatability, and accuracy, with the analytical range, limit of detection (LOD), and lower limit of quantification (LLOQ) varying notably among compounds. The method was used to calculate the excretion of phenyl‐γ‐valerolactones in healthy subject consuming green tea, providing novel information on the real concentrations of phenyl‐γ‐valerolactones in urine. Conclusion This work opens the door to better studying the bioavailability of flavan‐3‐ols and the real exposition to flavan‐3‐ol sources, as well as to define the bioactivity of these colonic metabolites in cell assays. This work described for the first time the synthetic procedure for 8 sulphate‐ and glucuronide‐conjugated phenyl‐γ‐valerolactones. A quick, selective, sensitive, reproducible, validated UHPLC‐ESI‐MS/MS method allowing the quantification of up to 13 phenyl‐γ‐valerolactones in human urine was developed. The analytical method allowed, for the first time, the accurate quantification of 10 phenyl‐γ‐valerolactones in urine samples of subjects consuming green tea, by using exact reference compounds.